Investigation of effect of hot-folio printability of mineral pigments - (:unkn) unknown (Scibulcom Ltd., 2017)
Hot-foil printing method is one of the post-printing methods widely used due to increasing attractiveness of cardboard packaging. It is the process of transferring a highly-polished metallic layers located on the carrier foil onto other surfaces by applying temperature and pressure. During the printing process, pigments are transferred to the carrying layer onto substrate by the heat effect. For a quality print, it is necessary to transfer pigments onto the substrate after pigments are completely separated from the carrying layer. In this stage, the surface properties of the substrate are important. In this study, the effect of hot-foil print of the paperboard coating was determined. For this purpose, five different coating formulations were prepared. In these formulations, while the percentages of pigments were changed, the ratios of binder and additives were kept constant. As a result of measurement, it was seen that the use of kaolin in the coating formulations increased the surface smoothness meanwhile decreasing the gloss. The surfaces coated with the formulation including calcium carbonate were more absorbent than the others. The mottle value was found to be increased in the prints, due to the use of hot-folio containing the sulphur element and the high content of the aluminium element. The light fastness of printed paperboard was calculated to be reduced owing to decreasing rate of calcium carbonate in coating formulations. Generally, upward ratio of kaolin in the coating formulations affected positively the light fastness of hot-folio printing. © 2017, Scibulcom Ltd. All rights reserved.
Keywords: Coating; Hot-folio; Mineral pigments; Packaging; Paperboard